Development of E-Module for Automation of Public Relations and Protocol Management using Articulate Storyline 3 - Risna DewiNur Haliza; Novi Trisnawati (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2023)
Education is a learning process that produces intelligent and educated individuals. The learning process is supported by lesson plans, media, and teaching materials. The development of teaching materials for E-Modules based on Articulate Storyline 3 is motivated by the limited ability of students to comprehend learning materials used in the form of printed books in Public Relations and Protocol subjects in class XII automation of office administration at state vocational high school 2 Buduran Sidoarjo, so that development is needed to support the learning process and make it easier for students to understand the material. This study aims to determine the feasibility of e-module teaching materials based on Articulate Storyline 3. It can be applied as teaching materials for class XII students in Public Relations and Protocol subjects. This development research uses the ADDIE development model, but is modified into Four (4) stages, namely:  1) Analysis, 2) Design, 3) Development, and (4) Implementation. Based on the results of the material expert validation, the Articulate Storyline 3-based Public Relations e-module obtained a score of 67 which was included in the " Appropriate " criteria. The results of linguist validation obtained a score 62, which was included in the "Appropriate" criteria. The results of the graphic expert validation obtained a score of 84 which is included in the "Very Appropriate" criteria. The results of student responses obtained a score of 94 including the criteria "Very Appropriate". Based on the results of expert validation and student responses, the Public Relations and Protocol e-module based on Articulate Storyline 3 is declared suitable for use as teaching material.